FAKTOR INTERNAL DAN EKSTERNAL DALAM PENGEMBANGAN NILAI EKONOMI KOPI CODOT DI HUTAN KEMASYARAKATAN BERINGIN JAYA, KABUPATEN TANGGAMUS - Bella Audia; Hari Kaskoyo; Christine Wulandari; Rahmat Safe`i (Jurnal Belantara, 2019)
Codot coffee is robusta coffee which is eaten by codot (bat) and can be developed to increase farmers' income. The purpose of the research is to identify internal and external factors towards raising of the economic value of codot coffee. Data retrieval is done by interviewing HKm Beringin Jaya farmers and Himawari Farmers Group, observation, and documentation study. Data was analyzed by descriptively qualitative. The results showed internal factors that influence of the economic value of codot coffee, namely: 1) the suitability of geographical location, 2) very affordable accessibility, 3) good quality of codot coffee, 4) production technology already supports, 5) knowledge of the benefits of less codot coffee, and 6) shade of coffee plants is still lacking. Influence external factors, namely: 1) the rapid development of codot coffee demand, 2) the rapid development of information and communication technology, 3) the business partners outside district of Tanggamus, 4) the stable price of codot coffee, 5) the uncertainty of weather effects, and 6) various competitors from other types of coffee. Extension education is needed to increase knowledge about the benefits and advantages of codot coffee; in addition partnerships with other private sectors need to be developed to improve marketing.